Cultural Tourism Management by the Local Knowledge of Lantan Ethnic Group, Nam Dee Village, Lao PDR - Saeliao, Thanyalak; Sivilay, Thongbay (Area Based Development Research Journal, 2018)
The study investigates the cultural tourism management of Lantan ethnic group in Nam Dee village, the province of Luang Namtha, Lao PDR, and explores the cultural tourism network of the ethnic group. The research employs qualitative research methodology approach and Participatory Action Research (PAR) which includes a field study, in-depth interviews, participant observation, field notes, and training. The results of the research signify the potential and wisdom in cultural tourism management of Lantan ethnic group at the village level. Their capabilities are observed in various aspects: 1) tourism management, 2) activity and profit sharing, and 3) the applications of natural resource management, knowledge on environments, social norms, local customs and culture, all of which lead to relationships with others at different levels. The community management is independent as long as it keeps the community moving forward and learning to adapt to the changes in contemporary world. However, in terms of unity in tourism management, the community has its weaknesses for being unable to fully self-function, and having to overly rely on outsourced organizations and external agencies. The development guidelines for cultural tourism network of ethnic villages in Luang Namtha, Laos PDR suggest to be an educational tourism and cultural exchange networks in which a learning community emerges between the tourists and the locals. For instance, a tour group visits the village and observes the local ways of life, fabric weaving, spinning, dyeing, and bamboo pulp paper making processes. For cultural tourism activities, it is emphasized that the Lantan ethnic group focuses on living a slow life, eating clean food and running green economy, from which the visitors learn a simple lifestyle and the green way of local productions.